Echocardiographic Epicardial Adipose Tissue Thickness as a Marker of Insulin Resistance - Tan-Ramos, Kristine Catherine; Sy, Rosa Allyn; Choa, Vivian (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Objective. The main objective of this study is to determine if epicardial fat thickness can be an early marker of insulin resistance. The specific objectives are to determine the specific thickness of epicardial fat that will correlate with insulin resistance and to correlate epicardial fat thickness with co-morbidities, anthropometric measurements and other clinical variables. Methodology. Patients were enrolled into the study by purposive sampling. Insulin assay, fasting blood sugar (FBS) and 2D echocardiogram measuring the epicardial fat were requested. HOMA-IR was computed and correlated with epicardial fat thickness. SPSS version 19 and Epi info v3.5.1 were used for statistical analysis. Linear regression analysis was performed on all variables to identify correlates with epicardial fat thickness. Results. A total of 22 subjects were included in the study. Insulin resistance determined using HOMA-IR, as well as BMI and fasting insulin level showed significant correlation with epicardial fat thickness (p-value <0.01). Based on the analysis, 9.5 mm was found to be the most sensitive and specific measurement for epicardial fat thickness that is correlated to insulin resistance with sensitivity of 100% and specificity of 86%. Conclusions. Epicardial fat thickness through routine 2D echocardiogram is significantly directly correlated with insulin resistance and 9.5 mm is the cut–off value for predicting insulin resistance.